2015
DOI: 10.1155/2015/650648
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Palatal Rugae in a Sudanese Population

Abstract: Palatal rugae patterns have unique characteristics and have been proposed as an alternative method to establish identity when other means, such as fingerprints and dental records, are not attainable. This study was conducted to determine the morphological characteristics of palatine rugae and to assess the existence of side asymmetry in them in Sudanese Arabs. It also assesses the possibility of determining sex using logistic regression. One hundred dental casts for 50 males and 50 females aged between 18 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
3
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
4
10
3
3
Order By: Relevance
“…The results of this study are partially in agreement with Ahmed and Hamid (2015) results who observed the predominance of forwarding than backward directed rugae. However, they mentioned that Sudanese males had significantly greater forwarding directed rugae than the Sudanese females.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study are partially in agreement with Ahmed and Hamid (2015) results who observed the predominance of forwarding than backward directed rugae. However, they mentioned that Sudanese males had significantly greater forwarding directed rugae than the Sudanese females.…”
Section: Discussionsupporting
confidence: 93%
“…During gestation, rugae are prominent and occupy most of the area of the palatal shelves (Ahmed and Hamid, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although palatal rugae, cranial and limb parameters have been used in sex estimation in adult Sudanese Arabs [31][32][33][34], the present study highlights the importance of sex assessment potential of ear variables that has not been explored before among the Sudanese. In considering the sex classification accuracy of the direct single variable discriminant analyses, the maximum classification accuracy obtained was 70% for the right ear and 68% for the left ear.…”
Section: Discussionmentioning
confidence: 93%
“…12 Penelitian lain tentang studi morfologi pada populasi sunda menghasilkan persentase arah rugae palatina paling sering muncul adalah forward (lebih dari 50%), diikuti dengan arah backward (lebih dari 30%). 29 Hasil uji statistik berdasarkan aspek arah menunjukkan nilai tidak signifikan, sehingga dapat disimpulkan bahwa berdasarkan klasifikasi arah, rugae palatina sebelum dan sesudah perawatan tidak terdapat perbedaaan. Hasil ini terlihat berbeda dengan penelitian lain yang menyatakan bahwa rugae palatina yang paling dekat dengan gigi lebih mudah untuk mengalami perubahan arah berkaitan dengan pergerakan gigi yang dilakukan.…”
Section: Pembahasanunclassified